1972
DOI: 10.1271/bbb1961.36.2357
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Extremely Thermophilic Bacteria from Hot Springs

Abstract: Isolation and Characterization of Extremely Thermophilic Bacteria from Hot Springs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…This suggests that the plasmid DNAs have high deoxyguanosine and deoxycytosine contents like their chromosomal DNA (69 to 70%) (Oshima & Imahori, 1971;Saiki et al, 1972). The large plasmid (pTF2) was present as only a single copy, whereas there were many copies of the small plasmids (pTF1, pTT8, pTF61 and pTF62).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the plasmid DNAs have high deoxyguanosine and deoxycytosine contents like their chromosomal DNA (69 to 70%) (Oshima & Imahori, 1971;Saiki et al, 1972). The large plasmid (pTF2) was present as only a single copy, whereas there were many copies of the small plasmids (pTF1, pTT8, pTF61 and pTF62).…”
Section: Discussionmentioning
confidence: 99%
“…The establishment of in vitro recombinant DNA techniques in an extreme thermophile should reduce the risks since these bacteria are obligate aerobes, are not parasitic, not sporeforming, and grow only above 45 "C with an optimum growth temperature of 60 to 72 "C (Oshima & Imahori, 1971 ;Saiki, Kimura & Arima, 1972). Furthermore, Lindsay & Creaser (1975) reported that thermostability of an enzyme was a transformable property between Bacillus species.…”
Section: Introductionmentioning
confidence: 99%
“…The Gram reaction is negative, and the cell wall has an outer layer that balloons out from the inner peptidoglycan at regular intervals (3, 49). Thermus strains have been isolated from hot springs and other thermal environments in the United States (2, 4, 5, 27,35,44,53), Iceland (1, 7, 18, 21-23, 32, 42), Belgium (€9, Britain (31), Portugal (26,39,47,48), the Czech Republic (34), Germany (15), the former USSR (24,25), Japan (28,29,37,45,46), New Zealand (16, 17), Thailand (20), and Kenya (51). Thermus isolates are usually yellow pigmented because they contain carotenoids, but colorless strains have been isolated from sources sheltered from light (2, 22,31,35,39,44).…”
mentioning
confidence: 99%
“…Microbes are present in nature in all environments [8,9] including air, rivers, sea, soil, body of plants and animals, and even in extreme conditions such as craters [10] or hot springs [11]. These exist in nature in different shapes such as spheres, rods, spirals, and icosahedrons, etc.…”
Section: Introductionmentioning
confidence: 99%